(untitled) (Latakia University Journal -Basic Sciences Series, 2017)
تؤدي عملية تشعيع عينة كريستالية إلى حصول تشوهات في هذه العينة ، وتنتج هذه التشوهات عن انزياحالذرات من أماكنها النظامية في الشبكة وتوضعها في أماكن غير نظامية كما تنتج هذه التشوهات ، لكن بمقدار أقل بكثير ، من جسيمات الحزمة ( الجسيمات الغريبة ) المتوضعة داخل العينة . يتعلق عمق ومقدار هذه التشوهات بمتحولات التشعيع، ويمكن تحديد مقاطع التوزع العمقي للتشوهات بطريقة RBS (Rutherford Back Scattering) ، لكن حساسية هذه الطريقة غير كافية لتحديد التوزع العمقي لكثافة جسيمات الحزمة المتوضعة داخل العينة . يتعلق عمق توضع قمة مقطع RBS بشدة بزاوية توجيه قناة ما من العينة بالنسبة إلى حزمة التشعيع وكذلك بنوع القناة.حيث تنزاح قمة مقاطع RBSفي التشعيع القنوي نحو العمق مقارنة مع نظيرتها في التشعيع العشوائي ويتعلق مقدار هذا الانزياح بمتحولات التشعيع . يزدادارتفاع قمة مقاطع RBSمع زيادة جرعة التشعيع القنوي ، ويسمى الارتفاع الذي لايمكن تجاوزه بحالة الأمورف والجرعة الموافقة بجرعة الأمورف وتتعلق جرعة الأمورف أيضا بمتحولات التشعيع وخاصة درجة حرارة العينة. The radiating process of a crystalline sample cause damages in this sample .These damages composed mostly of displaced sample atoms from their regular position in lattice, and placed in irregular position, and of very less quantity from some beam particles ( strange particles ) , that placed inside of this sample. The depth and amount of these damages are correlating with radiating parameters. It’s possible to estimate the depth distribution profiles of damages by RBS-Method, but the sensitivity of this method is not enough to determine the depth distribution of concentration of beam particles , that placed inside of the sample . The placement depth of RBS-Profiles top is strongly correlated with orientation angle of a sample’s channel relative to radiating beam also to kind of channel ,whereas the RBS-Profiles top displaces in depth , in channel radiation compare with its counter part in random radiation and the displacement value correlates with radiation parameters The height of RBS-Profiles top increase by increasing of radiation dose, and height that can’t be survived called amorph state , and the agreeing dose called ,amorph dose , the amorph dose correlates also with radiation parameters, special sample temperature